Eksternalitas Positif Bendungan Way Sekampung Bagi Masyarakat Pekon Bumi Ratu Kecamatan Pagelaran Kabupaten Pringsewu - Lely Risna Sari; Heru Wahyudi; Resha Moniyana Putri; Moneyzar Usman (Journal on Education, 2025)
This research aims to examine the changes in economic and social conditions experienced by the community before and after the construction of the Way Sekampung Dam in Pekon Bumi Ratu, Pagelaran District, Pringsewu Regency. The study focuses on economic aspects, including 1) employment and business opportunities, 2) livelihoods, and 3) income, as well as social aspects such as public facilities. A descriptive method with a qualitative approach was applied in the research, utilizing the Wilcoxon Signed Rank Test for data analysis. The findings indicate significant differences in economic conditions, such as increased employment and business opportunities, changes in livelihoods, and higher incomes. Additionally, improvements in social conditions, particularly public facilities, were observed following the dam's construction, benefiting the community in Pekon Bumi Ratu.